Combination of fucoidan-based magnetic nanoparticles and immunomodulators enhances tumour-localized immunotherapy - Chiang, Chih-Sheng; Lin, Yu-Jung; Lee, Rachel; Lai, Yen-Ho; Cheng, Hung-Wei; Hsieh, Chia-Hung; Shyu, Woei-Cherng; Chen, San-Yuan (Nature nanotechnology, 2018)
Checkpoint immunotherapy that inhibits tumour immune evasion has demonstrated significant clinical success. However, the therapeutic response is limited to certain patient populations, and immunotoxicity as well as autoimmunity have compromised the therapeutic benefits. Here, we report on an inherently therapeutic fucoidan–dextran-based magnetic nanomedicine (IO@FuDex 3 ) conjugated with a checkpoint inhibitor (anti-PD-L1) and T-cell activators (anti-CD3 and anti-CD28). IO@FuDex 3 can repair the immunosuppressive tumour microenvironment by reinvigorating tumour-infiltrating lymphocytes, while targeting the nanomedicine via magnetic navigation to the tumour to minimize off-target effects. Treatment that combines IO@FuDex 3 and magnetic navigation reduces the occurrence of adverse events and extends the median survival from 32 to 63 days with less than 1 per cent dose compared with soluble anti-PD-L1. Thus, we demonstrate the potential of integrating anti-PD-L1 and T-cell activators as a form of inherently therapeutic nanomedicine to augment the therapeutic index of combination checkpoint immunotherapy. Magnetic fucoidan-based nanoparticles conjugated with T-cell activators and checkpoint inhibitors can be directed to tumours via magnetic navigation for improving therapeutic efficacy and reducing systemic side effects.